Anti-predator behaviour of Cape fur seals Arctocephalus pusillus pusillus in relation to predation by white sharks Carcharodon carcharias around Seal Island, False Bay, South Africa - De Vos, Alta (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 161-202).